Determination of the Role of Different Surface Functional Groups on EDA Modified Rice Hull in the Sorption of Dyes - Ong, Siew-Teng; Keng, Pei-Sin; Lee, Chnoong-Kheng (Asian Journal of Chemistry, 2012)
The effectiveness of using ethylenediamine modified rice hull to remove basic blue 3 and reactive orange 16 dyes from aqueous solution was carried out. In order to determine the role of the surface functional groups of rice hull in the sorption of dyes, these surface functional groups were subjected to different chemical modifications. Results indicate that carboxyl group was the major functional group involved in the sorption of basic blue 3, whereas for the binding of reactive orange 16 occurs through the interaction with amino groups.